Journalistikkens rolle i netværkssamfundet - Mark Ørsten (Journalistica, 2007)
In the network society the boundaries between media, politics, economy and culture is put under pressure. The media is placed in an increasingly direct competition with the state, private companies, interest organisations etc. about the powers of definition within important spheres of society. This is illustrated by for instance “the Muhammad crisis” and the debate about the documentary “The secret war”. Both cases also show the importance of the legitimacy of the roles played by the media in the network society. This puts forward the old question about the objectivity of journalism, and makes this question important in the debate about the roles of journalism in the network society.